Long-term results of using the skin test with tuberculosis recombinant allergen for tuberculosis detection in Stavropol Region - O. D. Baronova; V. S. Odinets; N. N. Moiseeva; T. V. Terekhina; S. A. Аkinina (Туберкулез и болезни лёгких)
The objective of the study: to evaluate the eﬀectiveness of the introduction of screening for tuberculosis using the skin test with tuberculous recombinant allergen (TRA) in children and adolescents in Stavropol Region. Subjects and methods. The method of continuous sampling was used for retrospective analysis of files of 1,112 patients with respiratory tuberculosis in Stavropol Region. There were two time periods distinguished: 2009-2011 and 2016-2018. In 2009-2011, Mantoux test with 2 TU PPD-L was used for screening for tuberculosis in children and adolescents, and in those 15 years old and older, ﬂuorography could be used. Among those of 18-24 years old, ﬂuorography was the only method used. In 2016-2018, a skin test with TRA was used for screening for tuberculosis in children of 8-17 years old. Results. In the clinical structure of tuberculosis in children of 0-14 years old in both periods, the primary forms prevailed. During Period II, the primary tuberculosis complex was detected statistically significantly more often compared to Period I: 31/113 (27.4%) and 11/113 (9.7%) (p < 0.01; χ2), which was associated with the additional examination of individuals selected based on results of the test with TRA, using spiral computed tomography of the chest, which provided good visualization of this form of tuberculosis. When tuberculosis was detected in adolescents (15-17 years old), the test with TRA demonstrated statistically significant higher efficacy – 46.9% (15/32 of all detected) compared to Mantoux test with 2 TU – 1.5% (1 / 65 of all detected), p < 0.01; χ2. In Period II, the structure of clinical forms of tuberculosis among adolescents improved due to increased incidence of focal tuberculosis from 16.7% (Period I) to 32.5% (p < 0.05) and decrease in the frequency of lung destruction from 33/84 (39.2%) (Period I) to 3/40 (7.5%), p < 0.05; χ2. Bacillary excretion was registered in 21/84 (25.0%) of the adolescents (Period I) and in 3/40 (7.5%) of them (Period II), p < 0.05; χ2. Dispensary follow-up over preventive treatment in children with a positive and hyperergic reaction to the test with TRA provided a positive eﬀect on the frequency of respiratory tuberculosis development in young people (18-24 years). In the period from 2009 to 2018, the incidence (per 100,000 population) decreased by 69.8%.